Environment type and storage period on eggshell quality of laying hens at different ages - Camargo,Sarah Maria Pires (2022)
ABSTRACT: Eggshell quality is directly linked to the good acceptability of the product by consumers, whereas the industry is concerned with economic losses. Prolonged periods of laying, diseases, nutrition, bird age and genetics can influence egg quality. This study aimed to examine the influence of the environment, bird age and storage period on the physical characteristics of the shell of eggs from commercial laying hens. The experiment involved 288 eggs from Hy-line hens, which were distributed in a completely randomized design with a triple 3×2×4 factorial arrangement represented by three ages (31, 62 or 88 weeks), two storage temperatures (ambient or refrigerated), and four storage periods (one, 10, 20 or 30 days), totaling 24 treatments. Four replications were used with three eggs each. Eggshell strength, percentage and thickness were measured. Differences were observed, with the eggs stored at room temperature exhibiting lower shell strength. Laying eggs at an advanced age (88 weeks) resulted in decreased eggshell strength as compared with the other ages, whereas the eggs from young layers (31 weeks) had a thicker shell. The advancing age of the laying hens reduced eggshell quality, regardless of the storage environment. Nonetheless, the eggs stored in the refrigerator showed better eggshell quality and integrity than those stored at ambient temperature.